People's Republic of China-Hong Kong Special Administrative Region : Staff Report for the 2000 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2001)
The People's Republic of China showed an impressive rapid economic recovery following the Asian crisis. Executive Directors commended the prudent banking practice, and stressed the need to maintain fiscal and monetary stances. They appreciated the Hong Kong Special Administrative Region's (SAR) rules-based approach to economic policy and the country's participation in the Financial Sector Assessment Program. They welcomed Hong Kong SAR's compliance with the Special Data Dissemination Standard, and urged the authorities to present monetary survey and fiscal accounts on a standardized international format.